Reversing Democracy: Examining the Nagari Institution in West Sumatra, Indonesia - Valentina, Tengku Rika; Putera, Roni Ekha; Irawati, Irawati (UI Scholars Hub, 2019)
Democracy consolidation is a process that reduces the possibility of reversing democratization, for the process is featured by negotiations among actors that wants to